Stem Cells in the Treatment of Renal Allograft Diseases - Nikonenko, O.S.; Rusanov, I. V.; Nykonenko, T. N.; Vildanov, S. R. (Transplantation and artificial organs, 2021)
In recent years, there has been growing interest in the use of stem cells as a therapeutic agent for the restoration of the damaged tissues and organs. We present a clinical case. Male, 39 y.o. Diagnosis: Glomerulonephritis. On 10/09/2012, he underwent heterotopic renal allotransplantation from a live relative donor. On 09/23/2020, he was admitted to the hospital due to renal allograft pyelonephritis. On 10/28/2020, a cell based donor umbilical cord blood product was infused. Cell therapy enabled to minimize the consequences of the graft damage, to preserve the graft function and satisfactory condition of the recipient.